Application of The Tri Core Breastfeeding Model Using Audiovisual-Based E-Modules to Increase The Motivation Of Working Mothers in Exclusive Breastfeeding in The Working Area of The Wonoayu Sidoarjo Health Center - Domas Nurchandra Pramudianti; Titi Maharrani; Evi Yunita Nugrahini; Aida Amaliya; Mohammad Hamiduzzaman (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The tri core breastfeeding model is a health education model for breastfeeding mothers that includes three main aspects: lactation education, self-efficacy or increased confidence in breastfeeding mothers, and support from the surrounding environment. The importance of increasing self-confidence when breastfeeding, especially in working mothers, is something that needs to be considered. The government's efforts to increase exclusive breastfeeding coverage are contained in Government Regulation No.33/2012 on breastfeeding. This study aims to analyze the application of tri core breastfeeding models using audiovisual-based e-modules to increase the motivation of working mothers in exclusive breastfeeding. This study used a quasy experiment method with a non-equivalent control group design. The intervention group (18 people) used e-modules, while the control group used e-leaflets (18 people). The results of this study obtained ρvalue 0.000 < α = 0.05. It can be concluded that there is a significant difference between the use of audiovisual-based e-module media and e-leaflets on increasing motivation for exclusive breastfeeding in working mothers. Data analysis in this study used marginal homogeneity test and mann whitney test. The application of tri core breastfeeding models using audiovisual-based e-modules is expected to be able to increase exclusive breastfeeding coverage in working mothers.